2020
DOI: 10.3390/ijerph17041259
|View full text |Cite
|
Sign up to set email alerts
|

Causation Analysis of Hazardous Material Road Transportation Accidents Based on the Ordered Logit Regression Model

Abstract: Understanding the influence factors and related causation of hazardous materials can improve hazardous materials drivers’ safety awareness and help traffic professionals to develop effective countermeasures. This study investigates the statistical distribution characteristics, such as types of hazardous materials transportation accidents, driver properties, vehicle properties, environmental properties, road properties. In total, 343 data regarding hazardous materials accidents were collected from the chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…It was concluded that the causes, location, types, time of occurrence, hazard class for materials involved, and consequences were determined. Recently, Ma et al [17] investigated causation analysis of Hazmat transportation accidents based on ordered logit regression model. The results gave ten significant factors related to accident severity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was concluded that the causes, location, types, time of occurrence, hazard class for materials involved, and consequences were determined. Recently, Ma et al [17] investigated causation analysis of Hazmat transportation accidents based on ordered logit regression model. The results gave ten significant factors related to accident severity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many methods for analyzing the relationships among the causes that may lead to accidents and the corresponding possible consequences are available, which can be categorized as statistic regression models (i.e., multivariate regression and multinomial logit) [1,[14][15][16][17][18] and machine learning methods (typical as Bayesian network and decision tree) [19][20][21][22][23]. Desai et al [1] presented a sequence of statistical models (i.e., partial least squares, spline regression, and Box-Cox transformations) to estimate the population affected and the impact of the cost incurred as a result of hazmat accidents.…”
Section: Cause-consequence Analysismentioning
confidence: 99%
“…Statistical analysis is used to determine the characteristics of accidents and to pave the way for accident prevention [ 10 ]. Statistical analyses of fatal accidents have been conducted in other hazardous industries, such as the mining [ 11 ], automotive [ 12 ], and chemical industries [ 13 ]. Dursun analyzed explosion-related accidents in Turkish coal mines caused by methane gas from 2010 to 2017 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that mortality from gas explosion accidents accounted for 68.34% of all fatal accidents. Using 343 cases, Ma et al analyzed the influence of road characteristics on accidents in China [ 12 ]. Jung et al investigated the main causes of chemical accidents in South Korea from 2008 to 2018 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%